CAUSATIVE ORGANISMS AND THEIR DRUG SENSITIVITY PATTERN IN ASCITIC FLUID OF CIRRHOTIC PATIENTS WITH SPONTANEOUS BACTERIAL PERITONITIS - Haider, Iqbal; Ahmad, Ibrar; Rashid, Ahmar; Bashir, Hamid; Faheem, Muhammad (Journal of Postgraduate Medical Institute, 2011)
Objectives: To find out the relative frequencies of various etiologic pathogens and their sensitivity pattern in ascitic fluid of cirrhotic patients with spontaneous backrid patients. Material and Methods: This prospective observational study was conducted at Lady Reading Hospital Peshawar from July 2004 to April 2005 on 50 patients with established diagnosis of cirrhosis liver with possible diagnosis of spontaneous bacterial peritonitis (SBP). A questionnaire was designed comprising detailed history, general physical examination, history of alcoholism, history of upper GI bleed and features suggestive of SBP. Results: Study included 50 patients (30 male and 20 female) ranging in age from 18-72 years with mean age of 47.02+13.43 years. Ascitic fluid culture was positive by blood culture bottle method (BCBM) in 42(84%) cases. The relative frequencies of classical SBP, bacter-ascites (BA) and culture negative neutrocytic ascites (CNNA) by the BCBM were 36 (72%), 06 (12%) and 08 (16%) respectively. Gram negative enterobacteria were detected by BCBM in 30 (60%) cases. E. coli was the commonest organism isolated in 15 cases (30%) followed by Klebsiella pneumonia in 7 cases (14%). All gram negative organisms showed good sensitivity for quinolone, cefotaxime and ceftriaxone. Gram positive bacteria were isolated from 12 (24%) cases by BCBM with Streptococcus pneumonia as the commonest organism from 8 (16%) patients. Gram positive isolates showed good sensitivity to amoxicillin-clavulanic acid, cefotaxime and ceftriaxone. Conclusion: Bedside inoculation of the ascitic fluid in blood culture bottles results in earlier growth detection and subsequent start of specific antibiotic therapy which is the main goal of SBP treatment.